2016
DOI: 10.18632/oncotarget.13598
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of hematologic malignant cell lines resistant to oncolytic virus treatment

Abstract: Pexa-Vec (pexastimogene devacirpvec; JX-594) has emerged as an attractive tool in oncolytic virotherapy. Pexa-Vec demonstrates oncolytic and immunotherapeutic mechanisms of action. But the determinants of resistance to Pexa-Vec are mostly unknown. We treated hemoatologic malignant cells with Pexa-Vec and examined the gene-expression pattern of sensitive and resistant cells. Human myeloid malignant cell lines (RPMI-8226, IM-9, K562, THP-1) and lymphoid cancer cell lines (MOLT4, CCRF-CEM, Ramos, U937) were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Immunotherapies with OVs and immune checkpoint inhibitors showed renewed promises for cancer treatment. However, many tumors are resistant to OVs27, 28, 29, 30 or fail to respond to checkpoint inhibitors 31, 32. When cells are infected by OVs, the virus replication causes tremendous stress on the host cells 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapies with OVs and immune checkpoint inhibitors showed renewed promises for cancer treatment. However, many tumors are resistant to OVs27, 28, 29, 30 or fail to respond to checkpoint inhibitors 31, 32. When cells are infected by OVs, the virus replication causes tremendous stress on the host cells 33 .…”
Section: Discussionmentioning
confidence: 99%
“…STAMBPL1 is the main factor of the JAMM family members. Additionally, previous studies have reported high expression levels of STAMBPL1 in cancer tissues and that knockdown of STAMBPL1 could suppress the biological activities of leukaemia via regulation of NF-κB activity (1214). In the present study, it was also demonstrated that STAMBPL1 protein expression was higher in gastric cancer tissues compared with that in adjacent normal tissues and that the expression levels increased with advanced stages in the clinical samples.…”
Section: Discussionmentioning
confidence: 97%
“…Increased expression of ILT2 on T cells was associated with poor response to oncolytic virotherapy using vaccinia virus [ 157 ]. Another study attempted to identify biomarkers associated with resistance to vaccinia virus therapy in hematological malignancies [ 158 ]. Genes involved in the ubiquitination pathway, DNA damage response and antigen presentation, among others, were identified and associated with resistance to vaccinia virus-induced oncolysis [ 158 ].…”
Section: Potential Biomarkers For Sensitivity To Oncolytic Virusesmentioning
confidence: 99%